Socio-Cultural Dynamics Challenges in Mental Health Issues and Human Rights in Indonesia - Lestari, Weny (Proceeding International Conference on Religion, Science and Education, 2025)
The increasing prevalence of mental health disorders in Indonesia demands urgent attention. Data of 2018 Basic Health Research showed that 6.1% of population above 15 years old experiencing depression and only 9% receiving treatment. Schizophrenia/Psychosis prevalence stands at 6.7 per mill, with 14% subjected to confinement, particularly in rural areas. Despite 85% seeking treatment, only 48.9% adhere to prescribed medication. The impact of the COVID-19 pandemic has further exacerbated mental health challenges, with socio-cultural stigma and confinement persisting as coping mechanisms. Family attitudes toward mental health remain a critical concern, impeding post-treatment care. Socio-cultural influences significantly affect detection, treatment, and post-treatment of mental health. The pervasive cultural stigma attributes mental health issues to mystical causes, perpetuating resistance to treatment and reliance on non-medical alternatives. Socio-cultural stigma and isolation compound the challenges on human rights especially on the rights to get the proper mental health’s treatment and information, negatively impacting individuals, families, and communities. Socio-cultural dynamics, poverty, limited access to healthcare, and inadequate support systems contribute to the complexity of mental health issues. Socio-culturally competence in community empowerment is crucial to foster awareness and early intervention, addressing the multifaceted challenges surrounding mental health in Indonesia.